Fault-tolerant consensus of nonlinear multi-agent systems with directed link failures, communication noise and actuator faults. Issue 1 (2nd January 2021) - Tariverdi, Abbas; Talebi, Heidar A.; Shafiee, Masoud
Abstract : This paper deals with the problem of fault-tolerant control (FTC) for a consensus of nonlinear multi-agent systems (MASs) with directed link failures/recoveries in the presence of communication noise and actuator faults. The directed link failures/recoveries model considered here is randomly switching topologies. Randomly switching topologies in MASs are governed by the Markovian jump process. Moreover, the actuator loss-of-effectiveness faults may happen in any of the actuators. To deal with this, by using the sliding mode control method and weak infinitesimal operation, a passive FTC strategy is presented and sufficient conditions for stochastic consensus of underlying MASs are derived in the mean square stability sense. To that end, by employing such FTC design, MASs achieve consensus in mean square sense onto the predefined stochastic sliding surfaces in finite time while robustness of the overall system against the directed link failures/recoveries and communication noise and actuator faults is guaranteed. Finally, an example on multiple networked Euler-Lagrange systems is presented to verify the effectiveness and feasibility of the proposed algorithms.